Health care resource utilization and characteristics of patients with eosinophilic asthma in secondary health care in Finland - Mika J. Mäkelä; Helene Nordahl Christensen; Antti Karlsson; Sarang Rastogi; Kirsi Kettunen (TAYLOR & FRANCIS LTD, 2022)
Background: Eosinophilic airway inflammation is common in asthma patients and appears to be associated with severe exacerbations and loss of asthma control.Objective: To describe the resource utilization and clinical characteristics of patients with eosinophilic asthma.Design: Asthma patients >= 18 years with >= 1 blood eosinophil count in secondary care (South West Finland) during 2003. 2013 were included. Clinical characteristics (age, lung function, body mass index, and comorbidities) and asthma-related resource utilization (hospital admissions, outpatient visits, and emergency room [ER] visits) were retrieved. Resource utilization rates were compared for patients with blood eosinophil <= or > 300 cells/mu L, using adjusted negative binomial regression models.Results: Overall, 4,357 eligible patients were identified (mean age 60 years, females 68%), of which 1,927 (44%) had > 300 eosinophil cells/mu L blood. Patients with <= 300 and > 300 eosinophil counts, exhibited similar clinical characteristics, including advanced age, poor lung function, and overweight. Comorbidities such as pneumonia, sinusitis, and nasal polyps, were more frequent among those with > 300 eosinophil cells/mu L blood compared with patients with lower counts. Eosinophil counts > 300 cells/mu L were associated with greater hospital admissions (rate ratio [RR] [95% confidence interval CI]: 1.13 [1.02; 1.24]) and outpatient visits (RR [95% CI]: 1.11 [1.03; 1.20]) compared with patients with lower eosinophil counts. Rates of ER visits were similar between the patient groups (RR [95% CI]: 0.99 [0.87; 1.12]).Conclusions: Hospital admissions and outpatient visits occurred more often for patients with eosinophil counts > 300 cells/mu L, than for patients with lower eosinophil counts. Routine blood eosinophil screening might be useful to identify patients with an eosinophilic phenotype eligible for more targeted treatments.